Evaluation of possible preventive activity of Elaeagnus angustifolia L. against osteoporosis, an in vivo study - Farid Niknam; Amir Azadi; Pouya Faridi; Nader Tanideh; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2016)
Evaluation of possible preventive activity of Elaeagnus angustifolia L. against osteoporosis, an in vivo study